Universal design in selected Philippine shopping mall restrooms - Padrigo, Jeanney P.
This case study aimed to assess and explore the practice of Universal Design in the local context. It evaluated the layouts, fixtures, finishes and clearances of selected ladies' restrooms in three Quezon City shopping malls. The purposive sampling method was used to gather data through ocular visits, photo documentations and actual measurements of clearances and fixtures. The data was treated by using tabulation, photo-criticism and content analysis. A data comparison was conducted to process the observations in accordance with the Philippine and American accessibility standards, recommended Universal finishes and fixtures, as well as the international principles and guidelines of Universal Design. The results showed that each of the ladies' restrooms exhibited some practical Universal Design applications, such as open entryways, elongated toilets, and toilet provisions for the disabled. On the other hand, inadequacies and non-compliance with Universal Design criteria were also observed in the form of small toilet cubicles, undersized door widths, and the lack of user-friendly fixtures. It was concluded that none of the selected restrooms were able to completely satisfy the standards, recommendations, and principles of Universal Design. However, it was noted that the limited but significant number of Universal Design applications - for instance, the use of motion-sensor faucets, full length mirrors and disable-friendly finishes - implied a good start to providing convenient and safe sanitary facilities for all. The researcher proposed minor alterations for the restrooms, specifically, the replacement of existing push-to-close faucets, use of light diffusers, and addition of adjustable toilet seats, among others. Also, future applications and further studies of Universal Design, perhaps involving men's restrooms, were recommended.